Assessment of the adaptive and phytoremediation potential of Miscanthus×giganteus grown in flotation tailings - Andrejić, Gordana; Šinžar-Sekulić, Jasmina; Prica, Milijana; Gajić, Gordana; Dželetović, Željko; Rakić, Tamara (Archives of Biological Sciences, 2019)
Paper description: Mining activities produce enormous amounts of metal contaminated flotation tailings which are devoid of vegetation cover, prone to erosion by wind and water and cause metal pollution and degradation of neighboring ecosystems. Miscanthus × giganteus plants were grown four months in flotation tailings with the aim of assessing its phytoremediation potential. All plants successfully grew, accumulated and retained the major portion of metals within roots, exhibited reduced plant growth and photosynthetic rate, whilst biochemical parameters were not affected. Miscanthus × giganteus is a metal excluder plant species that can be cultivated as a stabilizer of flotation tailings. Abstract: Mining activities produce enormous amounts of metal-contaminated waste that is the source of ecosystem pollution by metals. Owing to complex adverse environmental conditions, the surface of abandoned flotation tailings is completely devoid of vegetation cover and is therefore very susceptible to fluvial erosion, wind dispersal to neighboring ecosystems and leaching of heavy metals into ground waters. The aim of this study was to estimate the adaptive potential of Miscanthus×giganteus (Poaceae) to grow on flotation tailings without any input. In this field experiment, plants were grown for four months in flotation tailings and in unpolluted control chernozem soil. Plants accumulated and retained the major part of metals within their roots, exhibiting their very low transfer to aerial parts, which all define M.×giganteus as a phytoexcluder plant species. Plants grown in flotation tailings showed significant reduction in the net CO2 assimilation rate and growth parameters, and there was no negative impact on pigment content, maximum quantum yield of PSII photochemistry, lipid peroxidation level and total antioxidative capacity in leaves. The obtained results indicate that despite reduced growth, M.×giganteus can be cultivated for phytoremediation of flotation tailings. https://doi.org/10.2298/ABS190709051A Received: July 9, 2019; Revised: August 14, 2019; Accepted: August 15, 2019; Published online: August 30, 2019 How to cite this article: Andrejić G, Šinžar-Sekulić J, Prica M, Gajić G, Dželetović Ž, Rakić T. Assessment of the adaptive and phytoremediation potential of Miscanthus×giganteus grown in flotation tailings. Arch Biol Sci. 2019;71(4):687-96.